2013
DOI: 10.3233/ies-130484
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Myotest Pro wireless accelerometer in squat jumps

Abstract: BACKGROUND: Portable and cost-effective accelerometers can yield instantaneous results of force, power, and velocity, with minimum set-up time to assess muscle power. However, such devices must also produce both valid and reliable data. OBJECTIVE: The current study assessed the validity and reliability of the Myotest Pro wireless accelerometer (ACC). METHODS: Thirty physically active males performed two squat jump, on two separate sessions. The jump was recorded simultaneously by a force platform and ACC, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Twenty-one of the included articles tested validity of the IMU [ 23 , 24 , 27 , 34 , 46 , 48 , 49 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Nineteen of the included articles tested the reliability of the IMU [ 23 , 24 , 27 , 34 , 46 , 48 , 49 , 56 , 57 , 58 , 60 , 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 ]. Six of the included articles compared the IMU with linear transducers [ 23 , 27 , 32 , 48 , 62 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one of the included articles tested validity of the IMU [ 23 , 24 , 27 , 34 , 46 , 48 , 49 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Nineteen of the included articles tested the reliability of the IMU [ 23 , 24 , 27 , 34 , 46 , 48 , 49 , 56 , 57 , 58 , 60 , 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 ]. Six of the included articles compared the IMU with linear transducers [ 23 , 27 , 32 , 48 , 62 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six of the included articles compared the IMU with linear transducers [ 23 , 27 , 32 , 48 , 62 , 68 ]. Five of the articles compared the IMU with contact platform [ 56 , 58 , 59 , 60 , 67 ], while one of the articles [ 69 ] compared the IMU with field computation method. Finally, six of the articles compared the IMU with motion capture system [ 24 , 61 , 64 , 65 , 66 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the coefficient of determination value (r 2 = .727) supports the idea of less agreement between F ACC and F FP , meaning ACC should not be used to measure force during a CMJ. The accuracy of peak force estimation could be increased using the squat jump and place the accelerometer on the bar (Bampouras et al, 2013;Crewther et al, 2011;Mauch et al, 2014), where the accuracy of the ACC has been shown to increase with increasing loads (Crewther et al, 2011). Therefore, we recommend reconsidering the use of ACC to estimate peak force during unloaded vertical jumps.…”
Section: Tablementioning
confidence: 99%
“…Previous research has shown that accelerometers provide increasingly valid and reliable force and power output data as the external load of a movement increases (Bampouras, Relph, Orme, & Esformes, 2013;Comstock et al, 2011;Crewther et al, 2011), but there is a lack of research regarding the use of accelerometers during bodyweight movements such as the countermovement jump, which may be more appropriate for sports in which athletes do not have to provide force against an external resistance (e.g. athletics, soccer, basketball, tennis, etc.).…”
Section: Introductionmentioning
confidence: 99%